2018
DOI: 10.1159/000495307
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis for Adult Attention Deficit Hyperactivity Disorder: Sociological Patient Case Report of Cannabinoid Therapeutics in Finland

Abstract: This paper presents a detailed patient case report of a male patient who was diagnosed in adulthood (aged 33) with attention deficit hyperactivity disorder (ADHD) and treated initially with immediate-release methylphenidate (Ritalin® 10 mg twice daily). After experiencing adverse effects from prolonged use of this medication and afterwards other medications that were prescribed as alternatives, the patient discovered that cannabinoid therapeutics (CT) had been experimented inside the EU area to treat patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
(53 reference statements)
0
14
0
7
Order By: Relevance
“…Similarly, blurry boundaries have been found for cannabis, which some of our interviewees used as an “indirect cognitive enhancer” (Franke et al, 2016; Hupli et al, 2016). Medical cannabis is reported to hold therapeutic potential for treatment-resistant ADHD among adults (Hupli, 2018), while “recreational” cannabis remains the most widely used “illegal substance” among young people in Europe (EMCDDA, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, blurry boundaries have been found for cannabis, which some of our interviewees used as an “indirect cognitive enhancer” (Franke et al, 2016; Hupli et al, 2016). Medical cannabis is reported to hold therapeutic potential for treatment-resistant ADHD among adults (Hupli, 2018), while “recreational” cannabis remains the most widely used “illegal substance” among young people in Europe (EMCDDA, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research in this field needs to consider other drugs used for cognitive enhancement purposes beyond prescription stimulants. For instance, cannabis as a cognitive enhancer among students (Franke et al , 2016) and as a potential pharmacotherapy for ADHD (Hupli, 2018) requires further attention, as cannabis remains the most used illicit drug among young people in the two countries (European Monitoring Centre for Drugs and Drug Addiction, 2019). In addition to cannabis as a cognitive enhancer, so-called psychedelic microdosing (Hupli et al , 2019b) has been identified as an emerging trend among young people in Amsterdam (Nabben et al , 2018), further making the argument that cognitive enhancement takes different forms depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of CB1Rs was also observed in the prefrontal cortex of SHRs, suggesting potential hypoactivation of the CB1R [ 254 ]. Evidence from case studies also suggests an improvement in ADHD symptoms in response to cannabis and cannabinoids consumption [ 255 , 256 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%